Pre-service teachers' conceptions of authority: a combination of internal and external dimensions of the teacher-student relationship - Joinel Alvarez, Vanessa (Swiss Journal of Educational Research, 2024)
This article compares the concept of authority in 66 secondary school pre-service teachers (PST) with a model of authority derived from a meta-analysis. For the PST, authority cannot be established on the sole basis of status or personal qualities but is founded primarily on professional expertise (didactic expertise, expertise in the management of a learning environment, relational expertise). Our results also reveal that SPT lack resources when it comes to intervening in the face of transgressions, and that they predominantly propose punitive interventions based on the use of power. Finally, we document three contextual factors that influence authority in the classroom: group characteristics, student characteristics and family environment.